Collaborative product development - A groupware system based on service oriented architecture - Melo, Daniel do N. (2010)
Product Development (PD) can be enhanced through web-based collaboration of working teams. This collaboration enables professionals to work simultaneously on a same project, e.g. the development of a new product. Collaborative PD requires networking resources, and applications needed by collaborating teams in the design and management of product development projects. Using this collaborative approach to PD can bring benefits on cost and speed of development, and also on ideas, all important factors contributing for increased competitiveness of companies and industrial regions worldwide. This is an important objective of the Industrial District of Manaus, Brazil, where the results of the research work reported in this paper are intended to be firstly applied. This work explores two dimensions of the web based PD problem, namely the PD collaboration platform and the PD tasks and information management dimensions. An investigation was carried out into groupware applications and technology and also into tools for managing product development projects. This led to the proposal of a model of a collaborative system for new product development based on both the Service Oriented Architecture and the SCRUM project management framework. This paper describes the specification of software and hardware requirements for the proposed model and the collaborative tools to be used.